Tinjauan Pelaksanaan Retensi Dokumen Rekam Medis di Rumah Sakit Medistra Jakarta Selatan - Dewi Kisaputri; Noor Yulia; Nanda Aula Rumana; Puteri Fannya (Yayasan Literasi Sains Indonesia, 2023)
Retention is an activity to reduce medical record documents from storage shelves by moving inactive medical record documents from active file shelves to inactive file shelves by sorting them on storage shelves according to the year of visit. Inactive medical records are medical record documents that have reached 5 years and are never used again because the patient does not visit the hospital for treatment. This research method uses qualitative analysis. Based on observations and interviews at Medistra Hospital. Currently, the South Jakarta Medistra Hospital is carrying out retention of medical records, but it has not been completed due to a lack of medical record personnel, there is no distribution of retention scheduling and the large number of medical records has piled up, making it difficult for officers to carry out retention. Medistra Hospitals already have an active DRM In Retention/ Shrinkage SPO, but there is no special officer in the filling section who is also the distribution executor. Suggestions should the implementation of depreciation and destruction of medical records be carried out routinely and make a division of schedules for officers who will carry out the retention of inactive medical records..